Comparação entre os valores da pressão arterial sistêmica central e braquial em mulheres e homens idosos com hipertensão arterial sistêmica - Pelazza, Bruno Bordin (2017)
Background: Systemic arterial pressure (SBP) changes with aging. Central SBP has a stronger correlation with cardiovascular risk factors than brachial SBP. In the elderly, progressive arterial stiffness and the early reflection wave develop to the amplification of the pulse pressure (PP), as a consequence of the elevation of the systolic blood pressure (SP). Mortality due to cardiovascular diseases in postmenopausal women has a prevalence equal to or higher than men due to low levels of estrogen plasma. Objective: To compare the values of central and brachial systemic arterial pressure among women and men over 60 years of age with systemic arterial hypertension. Methods: A quantitative, descriptive, cross-sectional study with elderly patients admitted and selected from the spontaneous and programmed demand at the basic health units of Uberlândia-MG, between March 2013 and March 2014. We included 69 participants from the study and compared the Central and brachial PAS through the Sphygmocor® XCEL equipment (AtCor Medical, Sydney, Australia). Results: There were significant differences in the SP values of the entire population in the central SP vs the brachial SP 140 (21) vs 153 (23), mmHg and in the central PP vs brachial 55 (18) vs 70 (18), mmHg. Furthermore, females presented higher blood pressure levels than males, central SP 144 (23) vs 134 (16), mmHg and brachial 161 (26) vs 148 (18), mmHg, central PP 62 (17) vs 45 (14), mmHg and brachial 80 (21) vs 63 (15), mmHg, and this was significant. Conclusion: There were therefore significant differences in SP and PP pressure, both at the central and brachial levels in hypertensive elderly, observed in the total study population and between women and men.